Phantom lymphadenopathy. An association with chronic fatigue syndrome. Issue 927 (1st January 2003) - Shee, C D
Abstract : Ten patients with self diagnosed enlarged lymph glands were referred to a general medicine outpatient clinic and careful examination did not confirm lymphadenopathy. All patients also complained of severe chronic fatigue associated with aches and miscellaneous somatic symptoms, and fulfilled criteria for diagnosis of chronic fatigue syndrome (CFS). Phantom lymphadenopathy may be a symptom in some people with CFS, and possible reasons for this are discussed.